2012
DOI: 10.1080/07315724.2012.10720013
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Children Consuming Breakfast Regularly Have Better Motor Functional Skills and Are Less Overweight Than Breakfast Skippers

Abstract: This study clearly underlines the importance of breakfast for school-aged children: Children eating breakfast almost every day had better motor functional skills and a lower BMI than children not regularly eating breakfast. The study further hints at the importance of generally healthy nutritional habits with regard to both motor functional skills and healthy weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
18
2
5
Order By: Relevance
“…Skipping breakfast is associated with metabolic factors including high total cholesterol levels (Resnicow, 1991), low BMI (Baldinger, Krebs, Muller, & Aeberli, 2012), and effective appetite and blood glucose control (Pereira et al, 2011). However, in our study, increased breakfast consumption frequency revealed no significant effect on the risk for a high fasting glucose or triglycerides.…”
Section: Discussioncontrasting
confidence: 64%
“…Skipping breakfast is associated with metabolic factors including high total cholesterol levels (Resnicow, 1991), low BMI (Baldinger, Krebs, Muller, & Aeberli, 2012), and effective appetite and blood glucose control (Pereira et al, 2011). However, in our study, increased breakfast consumption frequency revealed no significant effect on the risk for a high fasting glucose or triglycerides.…”
Section: Discussioncontrasting
confidence: 64%
“…In an earlier Swiss study, children consuming breakfast frequently were shown to have a lower BMI compared to those skipping breakfast on a regular basis [28]. Similar findings were reported in other studies summarized by Rampersaud et al [29].…”
Section: Discussionsupporting
confidence: 53%
“…Ante este problema, las "universidades saludables" deben implementar programas nutricionales universitarios que sustituyan las bebidas gaseosas y/o azucaradas por bebidas saludables y naturales en las cafeterías universitarias. Los estudiantes de mayor ciclo tuvieron un mayor riesgo de este consumo, probablemente debido a que pasan la mayor parte de su tiempo en diversas sedes hospitalarias, donde la comida rápida y las gaseosas sean los alimentos y las bebidas más accesibles 11 . Otra explicación sería que con el pasar de los años estos estudiantes adquieren más libertad y corren el riesgo de desarrollar malos hábitos alimentarios.…”
Section: Discussionunclassified